Honey and its role in Medical disorders - Hamad Alfarisi, Hamad Abdulsalam; Ibrahim, Muhammad; Hamad Mohamed, Zenab; Hamdan, Asmah Hanim; Che Mohamad, Che Anuar (2021)
Honey has been used as food and medicine by ancient and modern world, and by all traditions and civilisations. Modern medicine has accepted honey as therapeutic agent for diversity of clinical ailments. Honey is a source of important macro and micronutrients, and a rich source of calories. Honey possesses modulating effects on most of risk factors of cardiovascular diseases (CVDs). Natural honey can exert hepatoprotective effects both in term of hepatic function as well as by preserving liver structure. Natural honey proven for its anti-inflammatory, antioxidant, antimicrobial, anticancer effects, and has been tried for wound healing, eye disorders, gastrointestinal diseases, neurological disorders, and fertility disorders. This review discusses the current knowledge for the important therapeutic role of honey.